Impact of metabolic Acidosis on the dialysis dose: findings from a two center cross-sectional study in a low income population setting. (2021)
Background: Metabolic acidosis (MA) still remains a very common finding in patients with end stage kidney disease (ESRD) despite the increasing volume of research on dialysis treatment that have resulted in improved haemodialysis delivery. Its occurrence increases the risk of dialysis termination and inadequate dialysis dose that is associated with poor treatment outcome. The study endeavored to study metabolic acidosis and to determine its relationship with the dialysis dose (Kt/V). Materials and Methods: This was a two centre cross-sectional study involving 298 participants with ESKD who had 1642 sessions of maintenance haemodialysis. Serum electrolytes were analyzed by the Ion-Selective Electrode method and haematocrit was determined using a Hematocrit Centrifuge Results: Two hundred and ninety eight (192 males and 106 females) participants took part with a mean age of 51.44 + 7.31 years (males, 51.18 + 4.62 years, females, 52.14 + 2.93 years), P=0.04. The mean serum bicarbonate concentration, post dialysis (20.61 ± 6.26 mmol/L) was significantly higher than the pre dialysis, 18.41 ± 3.63 mmol/L (P<0.001) concentration. The prevalence of pre and post dialysis metabolic acidosis were 79.0% and 38.3% (P<0.001) There was a significant reduction in the mean anion gap following dialysis (P<0.001). The mean dialysis dose was significantly higher in males than females (P=0.03) and in participants with normal PSBC than participants with low PSBC (P<0.001) Risk factors for metabolic acidosis were advancing age, elevated Body Mass Index and blood pressure. Metabolic acidosis was negatively related to glomerular filtration rate and haematocrit. Aging, lesser dialysis frequency, independently predicted metabolic acidosis Conclusion: Metabolic acidosis is quite common in patients on maintenance dialysis, more common in females, advancing age and in less frequent dialysis treatment. Its occurrence increased the risk of inadequate dialysis.